In situ evaluation of a timber structure using a drilling resistance device. Case study: Kjøpmannsgata 27, Trondheim (Norway). (21st August 2017) - Frontini, F.
Abstract : The aim of this study was to evaluate the structural health of a 19th-century warehouse located in Trondheim using a drilling resistance device. The building, Kjøpmannsgata 27, is one of the many bryggene which are situated along the river Nidelva. These buildings were used in the past as warehouses and repositories. They represent the peak period of the town's commercial expansion during the 18th and 19th centuries and are considered an important part of the city's historical profile. The building has many structural issues, especially in the basement where the structure is in direct contact with the ground. A visual survey of the building was carried out prior to drilling resistance testing. The combination of these two methods was used to locate decayed wood and critical areas in need of repair. The foundation beams were found to be in the worst state of decay. Measurement of the drilling resistance proved to be a useful method for evaluating the condition of the building's structure, providing the basis to plan its rehabilitation.